2021
DOI: 10.3389/fpsyt.2021.648501
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Use of Enhancement Drugs at the Time of the COVID-19 Pandemic: A Multicultural Study on Coping Strategies During Self-Isolation and Related Risks

Abstract: Introduction: Little is known about the impact of restrictive measures during the COVID-19 pandemic on self-image and engagement in exercise and other coping strategies alongside the use of image and performance-enhancing drugs (IPEDs) to boost performance and appearance.Objectives: To assess the role of anxiety about appearance and self-compassion on the practice of physical exercise and use of IPEDs during lockdown.Methods: An international online questionnaire was carried out using the Exercise Addiction In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 63 publications
3
51
0
Order By: Relevance
“…Mooney et al (2017) found in a sample of gym and fitness club users a risk of EA, appearance anxiety, and low self-esteem, as well as an inclination to use products to supplement their physical exercise protein (41%), caffeine (30%), nitric oxide (13%), and anabolic steroids (7%). In this same line, Dores et al (2021) found in a large sample, including the participants from Spain (15.7%), during the lockdown because the COVID-19, strong relations between physical exercise and use of image and performance-enhancing drugs, and, as in other studies, anxiety about appearance also increased the probability of using these drugs.…”
Section: Discussionsupporting
confidence: 73%
“…Mooney et al (2017) found in a sample of gym and fitness club users a risk of EA, appearance anxiety, and low self-esteem, as well as an inclination to use products to supplement their physical exercise protein (41%), caffeine (30%), nitric oxide (13%), and anabolic steroids (7%). In this same line, Dores et al (2021) found in a large sample, including the participants from Spain (15.7%), during the lockdown because the COVID-19, strong relations between physical exercise and use of image and performance-enhancing drugs, and, as in other studies, anxiety about appearance also increased the probability of using these drugs.…”
Section: Discussionsupporting
confidence: 73%
“…Although excessive exercising has been previously correlated with excessive IPEDs use during the COVID-19 physical distancing (Dores et al, 2021 ), this is the first study assessing the differences across various sport disciplines in terms of EAI, AAI, and SCS and their level of engagement in physical activity (AG vs. NAG).…”
Section: Discussionmentioning
confidence: 92%
“…This scale has 12 items reflecting on attitudes toward oneself (e.g., “when something painful happens, I try to take a balanced view of the situation”), resulting in its total scores ranging from 12 to 60. A high internal reliability was observed for the total sample (Cronbach's α = 0.82), and the questionnaire has been translated in different languages (Dores et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the web has been contributing to the diffusion of new synthetic compounds, such as designer benzodiazepines and illicit fentanyl analogs, which are associated with a high abuse potential and severe adverse effects including coma and death (26)(27)(28). Finally, since the beginning of 2020, due to drug shortage issues resulting to the COVID-19 pandemic, a shift in misusing behavior relating to both prescription and OTC medicines has been recorded (10,13,(29)(30)(31)(32)(33).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%